Comparison of Upper Extremities of Children Who Playing and Not Playing Basketball - Orhan Ahmet Şener; Şerife Alpa (Türk Spor ve Egzersiz Dergisi)
In this study, it is aimed to compare the upper extremities of children who play and do not play basketball. In this study, measurements were taken in the upper extremities of a total of 200 secondary school students playing basketball and non-playing, with a mean age range of 11 ± 1.08 (did play sports) - 11 ± 0.8 (did not play sports).  The average height and weight ratio of the students who did and did not play sports were 153.5 ± 12.9 - 149.2 ± 8.1 cm and 46.7 ± 12.04 - 43.08 ± 12.9 kg respectively. In the right and left upper extremities of the students who play sports, arm length was 28.4 ± 3.1 - 28.4 ± 3.01, the forearm length was 24.1 ± 2.4 - 24.1 ± 2.4, hand length was 15.9 ± 1.8 to 15.9 ± 1.6, arm circumference was 23.2 ± 3.9 - 23.0 ± 3.8, the circumference of forearm was 20.8 ± 2.5 - 20.6 ± 2.5, hand width was 7.8 ± 0.8 to 7.9 ± 0.8.